Mechanical Properties of High Viscosity Glass Ionomer and Glass Hybrid Restorative Materials - Ivan Šalinović; Matea Stunja; Zdravko Schauper; Željko Verzak; Ana Ivanišević Malčić; Valentina Brzović Rajić (University of Zagreb. School of Dental Medicine, 2019)
Objectives: to determine the mechanical properties of hybrid and high-viscosity glass ionomer cements. Compressive strength and hardness of three glass ionomer cements (GIC) were measured: Ketac ™ Universal Aplicap ™, EQUIA Fil® and EQUIA FORTE Fil®, and the SEM sample analysis were performed. Material and Methods: The samples for measuring the compressive strength were prepared using silicone molds with standard dimensions of 6 mm x 4 mm and stored in deionized water for five days, while the samples for hardness measurement were prepared using Teflon molds with a cylindrical opening in the middle, dimensions 2 mm in height and 5 mm in width. For each material, one sample was made (n = 1) and stored in deionized water at 37ºC for 25 days. A representative sample of each material was analyzed using SEM. For the comparison of obtained values, the ANOVA test was used, while Tukey test was used for the multiple comparison. Results: There were no significant differences between the compressive strength of the three tested materials (p <0.05). The hardness values were: 157 HV0,2 for Ketac ™ Universal Aplicap ™ , 47 HV0,2 for EQUIA Fil® and 39 HV0,2 for EQUIA FORTE Fil®, respectively, and were significantly different, implying that Ketac ™ Universal Aplicap ™ has much higher hardness values than the other materials tested. SEM sample analysis revealed similar fracture modes of the tested materials. Conclusion: It was concluded that there were no statistically significant differences in compressive strength and fracture modes between the tested materials, while Ketac ™ Universal Aplicap ™ hardness results were significantly higher than the ones measured for EQUIA Fil® and EQUIA FORTE Fil®.